Polyester base material laser carving master batch and preparation method thereof
By using special feeding sequence and compound stabilizer in the polyester substrate to prepare radium engraving masterbatches, the problem of poor laser engraving effect of polyester materials is solved, and efficient, uniform and accurate laser marking effect is achieved.
Patent Information
- Application Number
- CN202411631762.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-10
AI Technical Summary
The laser engraving and surface effect of existing polyester materials is not good enough to meet the needs of efficient labeling.
Using a special feeding sequence and compound stabilizer, including the mixture of radium engraving powder, titanium dioxide, pigment, compound stabilizer and dispersant, the radium engraving masterbatch is prepared by granulating the twin-screw extruder to improve the clarity of radium engraving. , uniformity and accuracy.
It significantly improves the clarity and durability of laser markings of laser engraving masterbatches, ensures the long-term stability and effect of the markings, and resists mechanical, chemical and physical erosion.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer material processing, and in particular to a polyester-based laser engraving masterbatch and a preparation method thereof. Background Art
[0002] Laser engraving uses the light energy of a laser beam to change the surface of a material and then leave marks. Laser engraving powder can help the material absorb laser energy and convert it into heat energy, so laser engraving powder is usually added to the material. After laser engraving, marks will appear on the surface of the material, but the clarity and surface effect of laser engraving on existing materials need to be further improved.
[0003] CN109370166A discloses a polyester material suitable for laser engraving and a preparation method thereof. The polyester material comprises the following components in parts by weight: 60-90 parts of poly(1,4-cyclohexane dimethanol terephthalate), 5-20 parts of a flame retardant, 0.5-10 parts of a laser engraving aid, 0.1-1 parts of an antioxidant, 0.1-1 parts of a lubricant, and 0.5-1 parts of a black masterbatch. The preparation method of the polyester material comprises: (a) adding PCT resin, a flame retardant, an antioxidant and a lubricant, and a laser engraving aid into a mixing and blending machine for mixing; (b) blending and granulating the mixture obtained in step (a) through a twin-screw extruder, and then melt-extruding and granulating to obtain a polyester composition. However, the laser engraving clarity and surface effect of the polyester material are still not good enough.
[0004] It can be seen that how to improve the laser engraving effect of polyester materials is a technical problem that needs to be solved urgently. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a polyester-based laser engraving masterbatch and a preparation method thereof. By adopting a special adding sequence and using a compound stabilizer, the laser engraving clarity, uniformity and accuracy of the polyester-based laser engraving masterbatch can be improved.
[0006] The present invention provides a polyester-based laser engraving masterbatch, which comprises the following components: Polyester substrate: 70-100 parts by weight; Laser carving powder: 1-20 parts by weight; Titanium dioxide: 0-20 parts by weight; Pigment: 0-5 parts by weight; Compound stabilizer: 0.1-1 parts by weight; Dispersant: 0.5-5 parts by weight; Cross-linking agent: 0.1-1 parts by weight.
[0007] Furthermore, the heat deformation temperature refers to the temperature point at which a material begins to change shape as the temperature rises under the action of an external force. The heat deformation temperature is an important indicator for measuring the heat resistance of a material.
[0008] Furthermore, when the pressure of the polyester substrate is 0.45 MPa, the thermal deformation temperature is 65-75°C.
[0009] Furthermore, the tensile strength of the polyester substrate is 23-28 MPa, the elongation at break is 100-130%, and the impact strength of the cantilever beam notch is 6.5-8 KJ / M 2 .
[0010] Furthermore, the polyester substrate is a type of PN200 or PN300 produced by SK Corporation of South Korea.
[0011] Furthermore, the polyester substrate is dried before preparing the laser engraving masterbatch, the drying temperature is 60-70° C., and the drying time is 6-12 hours.
[0012] Furthermore, the laser engraving powder can efficiently absorb the energy of the laser beam, and then quickly convert the absorbed laser energy into heat energy, producing a strong thermal effect on the polyester substrate. Therefore, after using the laser engraving powder, the clarity, uniformity and accuracy of the laser marking can be significantly improved, and the laser engraving powder is strong and durable, and can resist erosion by mechanical, chemical and physical factors, ensuring the long-term effectiveness of the marking.
[0013] Furthermore, the laser engraving powder is in powder form, with a particle size of 5-10um and a specific gravity of 1.5-2g / cm 3 , heat-resistant temperature is 200-300℃.
[0014] Furthermore, the model of the laser engraving powder is one of the types 8815, 8808, 8825 or 8850 in the Iriotec series produced by Merck & Co., USA.
[0015] Furthermore, the surface of the titanium dioxide is coated with zirconium aluminum, and the surface of the titanium dioxide is coated with zirconium oxide and aluminum oxide to form a coating layer with a pearlescent effect. This coating layer can significantly improve the reflective ability of the titanium dioxide, thereby greatly improving the gloss of the titanium dioxide. At the same time, the coating layer can effectively prevent the titanium dioxide from being directly exposed to the environment, thereby extending the service life and maintaining stability.
[0016] Furthermore, the titanium dioxide, as an important white pigment, acts as a whitening agent in the laser engraving powder, which can effectively improve the brightness of the laser engraving masterbatch and make the laser engraving pattern more visually vivid. At the same time, the titanium dioxide has excellent color stability, which can ensure that the laser engraving pattern maintains bright colors for a long time and is not easy to fade or discolor.
[0017] Furthermore, the titanium dioxide is a white powder, wherein the content of titanium dioxide is 95-97%, and the specific gravity of the titanium dioxide is 4.2-4.8 g / cm 3 .
[0018] Furthermore, the pigment has a coloring effect and a heat-resistant temperature of 260-350°C.
[0019] Furthermore, the compound stabilizer is a mixture of a heat stabilizer and a light stabilizer, and the ratio of the heat stabilizer to the light stabilizer is (1-10): (1-10).
[0020] Furthermore, when laser energy acts on the surface of the laser engraving masterbatch, the local temperature will rise rapidly. The addition of the thermal stabilizer can effectively prevent the laser engraving masterbatch from thermal degradation at high temperature, thereby ensuring the stability of its physical and chemical properties. Furthermore, the light stabilizer can absorb ultraviolet rays and convert them into heat energy, thereby preventing ultraviolet rays from directly irradiating the laser engraving masterbatch to cause photo-oxidation reaction, thereby reducing the destructive effect of ultraviolet rays on the laser engraving masterbatch, thereby avoiding yellowing and helping to extend the service life.
[0021] Furthermore, the heat stabilizer is a mixture of a metal soap stabilizer and an antioxidant, and the ratio of the metal soap stabilizer to the antioxidant is (1-10): (1-10).
[0022] Furthermore, the metal soap stabilizer is calcium stearate or zinc stearate.
[0023] Furthermore, the calcium content of the calcium stearate is 6-8%, and the melting point of the calcium stearate is 150-170°C.
[0024] Furthermore, the zinc content in the zinc stearate is 13-15%, and the melting point of the zinc stearate is 120-130°C.
[0025] Further, the antioxidant includes a primary antioxidant and a secondary antioxidant, the primary antioxidant is one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(2,4-di-tert-butylphenyl)phosphite or bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite, the secondary antioxidant is one of tris(2,4-di-tert-butylphenyl)phosphite, dilauryl thiodipropionate or bis(2,4-di-tert-butylphenol)sulfide, and the primary antioxidant and the secondary antioxidant are mixed in any proportion.
[0026] Furthermore, the light stabilizer is a mixture of phenylbenzotriazole and bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate, and the ratio of the phenylbenzotriazole to the bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate is (1-10):(1-10).
[0027] Furthermore, the dispersant is a mixture of a high molecular weight amino-modified silicone resin and a high molecular weight hyperbranched polymer, and the ratio of the high molecular weight amino-modified silicone resin to the high molecular weight hyperbranched polymer is (1-2): (1-2).
[0028] Furthermore, the viscosity of the high molecular weight amino-modified silicone resin is 6000-8000 mPa·s, and the dynamic friction coefficient is 0.09-0.18. The high molecular weight amino-modified silicone resin can improve the wear resistance of the laser engraving masterbatch.
[0029] Furthermore, the acid value of the high molecular weight hyperbranched polymer is 450-650 mgKOH / g, and the high molecular weight hyperbranched polymer can improve the fluidity and dispersibility of the laser carving masterbatch.
[0030] Furthermore, the cross-linking agent is diphenylmethane diisocyanate, which can significantly improve the mechanical strength of the polyester substrate by forming chemical bonds inside the polyester substrate and converting it into a three-dimensional network structure. At the same time, the laser engraving masterbatch after cross-linking has better heat resistance.
[0031] The present invention provides a method for preparing a polyester-based laser engraving masterbatch, the method comprising the following steps: Step 1: Weigh each component; Step 2: Mixing material: taking the laser carving powder, the titanium dioxide, the pigment, the compound stabilizer and the dispersant, stirring and mixing in a high-stirring pot to obtain a mixed material 1; Step 3: Mixing material: taking the polyester substrate and the cross-linking agent and stirring and mixing them in a high-stirring pot to obtain a mixed material 2; Step 4: Granulation: Take the mixed material 1 and the mixed material 2 and feed them simultaneously through the main feeding port of the twin-screw extruder, extrude them through the twin-screw extruder, cool them, and pelletize them to obtain the polyester-based laser engraving masterbatch.
[0032] Furthermore, in step 2, the stirring temperature of the high stirring pot is 65-85° C., the stirring speed is 200-300 r / min, and the stirring time is 1-3 min.
[0033] Furthermore, in step 3, the stirring temperature of the high stirring pot is 45-65° C., the stirring speed is 100-200 r / min, and the stirring time is 1-2 min.
[0034] Furthermore, in step 4, the processing temperature of the twin-screw extruder is 220-260°C.
[0035] Further, in step 4, the twin-screw extruder is divided into 12 temperature zones, the temperature of the first temperature zone is 220-245°C, the temperature of the second temperature zone is 225-250°C, the temperature of the third temperature zone is 225-250°C, the temperature of the fourth temperature zone is 225-255°C, the temperature of the fifth temperature zone is 225-260°C, the temperature of the sixth temperature zone is 225-260°C, the temperature of the seventh temperature zone is 230-260°C, the temperature of the eighth temperature zone is 240-260°C, the temperature of the ninth temperature zone is 240-260°C, the temperature of the tenth temperature zone is 245-260°C, the temperature of the eleventh temperature zone is 220-255°C, and the temperature of the twelfth temperature zone is 220-240°C.
[0036] Furthermore, in step 4, the screw speed of the twin-screw extruder is 200-400 r / min.
[0037] Furthermore, in step 4, the extruder head temperature of the twin-screw extruder is 220-240°C.
[0038] Furthermore, in step 4, the melt pressure of the twin-screw extruder is 6-10 MPa.
[0039] Furthermore, in step 4, the vacuum pressure of the twin-screw extruder is (-0.1) - (-0.05) MPa.
[0040] Furthermore, in step 4, the main engine current of the twin-screw extruder is 100-200A.
[0041] Furthermore, in step 4, the torque of the twin-screw extruder is 10-15 N·m.
[0042] Furthermore, in step 4, the aspect ratio of the twin-screw extruder is (48-60):1.
[0043] Furthermore, in step 4, the rotation speed of the pelletizer is 2500-3500 r / min, and the length of the laser engraved masterbatch is 2-4 mm.
[0044] Beneficial effects of the present invention 1. The prior art generally adopts a preparation method of directly mixing the components, while the present invention first mixes the laser engraving powder, titanium dioxide, pigment, compound stabilizer and dispersant, and then adds the mixture of polyester substrate and cross-linking agent. The present invention adopts a special adding sequence to make the small particle components mix evenly under the action of the dispersant. Therefore, the prepared polyester substrate laser engraving masterbatch has higher laser engraving clarity, uniformity and accuracy.
[0045] 2. The prior art generally uses metal soap stabilizers or antioxidants, while the present invention uses a compound stabilizer, which is a mixture of a heat stabilizer and a light stabilizer, wherein the heat stabilizer is a mixture of a metal soap stabilizer and an antioxidant, that is, the compound stabilizer of the present invention includes a metal soap stabilizer, an antioxidant and a light stabilizer, thereby effectively preventing thermal oxidative aging of polyester-based laser engraving masterbatch during the preparation process, and making the laser engraving clarity, uniformity and accuracy of the laser engraving masterbatch higher. DETAILED DESCRIPTION
[0046] Example 1 Preparation method of polyester substrate laser engraving masterbatch: Step 1: Weigh the following components: 70 parts by weight of polyester substrate, 1 part by weight of laser engraving powder, 0.1 parts by weight of compound stabilizer, 0.5 parts by weight of dispersant, and 0.1 parts by weight of crosslinking agent. When the pressure of polyester substrate is 0.45 MPa, the heat deformation temperature is 65°C, the tensile strength is 23 MPa, the elongation at break is 100%, and the impact strength of cantilever beam notch is 6.5 KJ / M 2 The polyester substrate is PN200 produced by SK Company of South Korea. The polyester substrate is dried before preparing laser engraving masterbatch. The drying temperature is 60℃ and the drying time is 6 hours. The laser engraving powder is in powder form with a particle size of 5um and a specific gravity of 1.5g / cm 3The heat-resistant temperature is 200℃. The model of laser engraving powder is 8815 in the Iriotec series produced by Merck in the United States. The compound stabilizer is a mixture of a heat stabilizer and a light stabilizer, and the ratio of the heat stabilizer to the light stabilizer is 1:1. The heat stabilizer is a mixture of a metal soap stabilizer and an antioxidant, and the ratio of the metal soap stabilizer to the antioxidant is 1:1. The metal soap stabilizer is calcium stearate, and the calcium content in calcium stearate is 6%. The melting point of calcium stearate is 150℃. The antioxidant includes a main antioxidant and an auxiliary antioxidant. The main antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and the auxiliary antioxidant is tris(2,4-di-tert-butyl The invention discloses a novel nanostructured polymer comprising a nanostructured polymer (N-butylphenyl) phosphite, a light stabilizer comprising a mixture of phenylbenzotriazole and bis-2,2,6,6-tetramethyl-4-piperidyl sebacate, wherein the ratio of phenylbenzotriazole to bis-2,2,6,6-tetramethyl-4-piperidyl sebacate is 1:1; a dispersant comprising a mixture of a high molecular weight amino-modified silicone resin and a high molecular weight hyperbranched polymer, wherein the ratio of the high molecular weight amino-modified silicone resin to the high molecular weight hyperbranched polymer is 1:1, the viscosity of the high molecular weight amino-modified silicone resin is 6000 mPa·s, the dynamic friction coefficient is 0.09, and the acid value of the high molecular weight hyperbranched polymer is 450 mgKOH / g; and a crosslinking agent comprising diphenylmethane diisocyanate.
[0047] Step 2: Mixing materials: Take the above-mentioned laser carving powder, compound stabilizer and dispersant, stir and mix them in a high-stirring pot to obtain mixed material 1, wherein the stirring temperature of the high-stirring pot is 65°C, the stirring speed is 200r / min, and the stirring time is 1min.
[0048] Step 3: Mixing material: Take the above polyester substrate and cross-linking agent and stir and mix them in a high-stirring pot to obtain a mixed material 2, wherein the stirring temperature of the high-stirring pot is 45°C, the stirring speed is 100 r / min, and the stirring time is 1 min.
[0049] Step 4: Granulation: Take mixed material 1 and mixed material 2 and feed them simultaneously through the main feeding port of the twin-screw extruder, extrude them through the twin-screw extruder, cool them, and cut them into pellets to obtain polyester-based laser engraving masterbatch. The twin-screw extruder is divided into 12 temperature zones, the temperature of the first temperature zone is 220°C, the temperature of the second temperature zone is 225°C, the temperature of the third temperature zone is 225°C, the temperature of the fourth temperature zone is 225°C, the temperature of the fifth temperature zone is 225°C, the temperature of the sixth temperature zone is 225°C, the temperature of the seventh temperature zone is 230°C, the temperature of the eighth temperature zone is 240°C, the temperature of the ninth temperature zone is 240°C, the temperature of the tenth temperature zone is 245°C, the temperature of the eleventh temperature zone is 220°C, and the temperature of the twelfth temperature zone is 220°C. The screw speed of the twin-screw extruder is 200 r / min, the extruder head temperature is 220℃, the melt pressure is 6MPa, the vacuum pressure is -0.1MPa, the main machine current is 100A, the torque is 10N·m, the aspect ratio is 48:1, the pelletizer speed is 2500r / min, and the length of the laser engraved masterbatch is 2mm.
[0050] Example 2 Preparation method of polyester substrate laser engraving masterbatch: Step 1: Weigh the following components: 85 parts by weight of polyester substrate, 10 parts by weight of laser engraving powder, 10 parts by weight of titanium dioxide, 3 parts by weight of pigment, 0.5 parts by weight of compound stabilizer, 3 parts by weight of dispersant, and 0.5 parts by weight of crosslinking agent. When the pressure of polyester substrate is 0.45 MPa, the heat deformation temperature is 68°C, the tensile strength is 25 MPa, the elongation at break is 112%, and the impact strength of cantilever beam notch is 7.1 KJ / M 2 The polyester substrate is PN300 produced by SK Company of South Korea. The polyester substrate is dried before preparing laser engraving masterbatch. The drying temperature is 65℃ and the drying time is 8 hours. The laser engraving powder is in powder form with a particle size of 7um and a specific gravity of 1.5g / cm 3 The heat-resistant temperature is 220℃. The laser engraving powder model is 8808 in the Iriotec series produced by Merck, USA. The surface of titanium dioxide is coated with zirconium aluminum. Titanium dioxide is a white powder with a titanium dioxide content of 95%. The specific gravity of titanium dioxide is 4.5g / cm 3The pigment is red and has a heat-resistant temperature of 300°C. The compound stabilizer is a mixture of a heat stabilizer and a light stabilizer, and the ratio of the heat stabilizer to the light stabilizer is 1:10. The heat stabilizer is a mixture of a metal soap stabilizer and an antioxidant, and the ratio of the metal soap stabilizer to the antioxidant is 1:10. The metal soap stabilizer is zinc stearate, and the zinc content in zinc stearate is 13%. The melting point of zinc stearate is 120°C. The antioxidant includes a primary antioxidant and a secondary antioxidant. The primary antioxidant is tris(2,4-di-tert-butylphenyl) phosphite, and the secondary antioxidant is dilauryl thiodipropionate. The light stabilizer is phenylbenzotriazole and diisopropyl ester. The invention discloses a mixture of 2,2,6,6-tetramethyl-4-piperidinyl sebacate, wherein the ratio of phenylbenzotriazole to bis-2,2,6,6-tetramethyl-4-piperidinyl sebacate is 1:10; the dispersant is a mixture of high molecular weight amino-modified silicone resin and high molecular weight hyperbranched polymer, wherein the ratio of high molecular weight amino-modified silicone resin to high molecular weight hyperbranched polymer is 1:2, the viscosity of the high molecular weight amino-modified silicone resin is 6500 mPa·s, the dynamic friction coefficient is 0.13, and the acid value of the high molecular weight hyperbranched polymer is 580 mgKOH / g; and the crosslinking agent is diphenylmethane diisocyanate.
[0051] Step 2: Mixing materials: Take the above-mentioned laser carving powder, titanium dioxide, pigment, compound stabilizer and dispersant, stir and mix them in a high-stirring pot to obtain mixed material 1, wherein the stirring temperature of the high-stirring pot is 75°C, the stirring speed is 250r / min, and the stirring time is 2min.
[0052] Step 3: Mixing material: Take the above polyester substrate and cross-linking agent and stir and mix them in a high-stirring pot to obtain a mixed material 2, wherein the stirring temperature of the high-stirring pot is 55° C., the stirring speed is 150 r / min, and the stirring time is 1 min.
[0053] Step 4: Granulation: Take the mixed material 1 and the mixed material 2 and feed them simultaneously through the main feeding port of the twin-screw extruder, extrude them through the twin-screw extruder, cool them, and cut them into pellets to obtain the polyester base laser engraving masterbatch. The twin-screw extruder is divided into 12 temperature zones, the temperature of the first temperature zone is 230°C, the temperature of the second temperature zone is 235°C, the temperature of the third temperature zone is 235°C, the temperature of the fourth temperature zone is 235°C, the temperature of the fifth temperature zone is 235°C, the temperature of the sixth temperature zone is 235°C, the temperature of the seventh temperature zone is 240°C, and the temperature of the eighth temperature zone is 240°C. The temperature of the first temperature zone is 250℃, the temperature of the ninth temperature zone is 250℃, the temperature of the tenth temperature zone is 255℃, the temperature of the eleventh temperature zone is 230℃, and the temperature of the twelfth temperature zone is 230℃. The screw speed of the twin-screw extruder is 300r / min, the extruder head temperature is 230℃, the melt pressure is 8MPa, the vacuum pressure is -0.08MPa, the main engine current is 150A, the torque is 13N·m, the aspect ratio is 55:1, the speed of the pelletizer is 3000r / min, and the length of the laser engraving masterbatch is 3mm.
[0054] Example 3 Preparation method of polyester substrate laser engraving masterbatch: Step 1: Weigh the following components: 100 parts by weight of polyester substrate, 20 parts by weight of laser engraving powder, 20 parts by weight of titanium dioxide, 5 parts by weight of pigment, 1 part by weight of compound stabilizer, 5 parts by weight of dispersant, and 1 part by weight of crosslinking agent. When the pressure of polyester substrate is 0.45 MPa, the heat deformation temperature is 75°C, the tensile strength is 28 MPa, the elongation at break is 130%, and the impact strength of cantilever beam notch is 8 KJ / M. 2 The polyester substrate is PN300 produced by SK Company of South Korea. The polyester substrate is dried before preparing the laser engraving masterbatch. The drying temperature is 70℃ and the drying time is 12 hours. The laser engraving powder is in powder form with a particle size of 10um and a specific gravity of 2g / cm 3 The heat-resistant temperature is 300℃. The laser engraving powder model is 8825 from the Iriotec series produced by Merck in the United States. The surface of titanium dioxide is coated with zirconium aluminum. Titanium dioxide is a white powder with a titanium dioxide content of 97%. The specific gravity of titanium dioxide is 4.8g / cm 3The pigment is green and has a heat-resistant temperature of 350°C. The compound stabilizer is a mixture of a heat stabilizer and a light stabilizer, and the ratio of the heat stabilizer to the light stabilizer is 10:1. The heat stabilizer is a mixture of a metal soap stabilizer and an antioxidant, and the ratio of the metal soap stabilizer to the antioxidant is 10:1. The metal soap stabilizer is calcium stearate, and the calcium content in calcium stearate is 8%. The melting point of calcium stearate is 170°C. The antioxidant includes a primary antioxidant and an auxiliary antioxidant. The primary antioxidant is bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite, and the auxiliary antioxidant is bis(2,4-di-tert-butylphenol) sulfide. The light stabilizer is phenylbenzo The invention discloses a mixture of triazole and bis-2,2,6,6-tetramethyl-4-piperidinyl sebacate, wherein the ratio of phenylbenzotriazole to bis-2,2,6,6-tetramethyl-4-piperidinyl sebacate is 10:1; the dispersant is a mixture of high molecular weight amino-modified silicone resin and high molecular weight hyperbranched polymer, wherein the ratio of high molecular weight amino-modified silicone resin to high molecular weight hyperbranched polymer is 2:1, the viscosity of the high molecular weight amino-modified silicone resin is 8000 mPa·s, the dynamic friction coefficient is 0.18, and the acid value of the high molecular weight hyperbranched polymer is 650 mgKOH / g; and the crosslinking agent is diphenylmethane diisocyanate.
[0055] Step 2: Mixing materials: Take the above-mentioned laser carving powder, titanium dioxide, pigment, compound stabilizer and dispersant, stir and mix them in a high-stirring pot to obtain mixed material 1, wherein the stirring temperature of the high-stirring pot is 85°C, the stirring speed is 300r / min, and the stirring time is 3min.
[0056] Step 3: Mixing material: Take the above polyester substrate and cross-linking agent and stir and mix them in a high-stirring pot to obtain a mixed material 2, wherein the stirring temperature of the high-stirring pot is 65° C., the stirring speed is 200 r / min, and the stirring time is 2 min.
[0057] Step 4: Granulation: Take mixed material 1 and mixed material 2 and feed them simultaneously through the main feeding port of the twin-screw extruder, extrude them through the twin-screw extruder, cool them, and cut them into pellets to obtain polyester-based laser engraving masterbatch. The twin-screw extruder is divided into 12 temperature zones, the temperature of the first temperature zone is 245°C, the temperature of the second temperature zone is 250°C, the temperature of the third temperature zone is 250°C, the temperature of the fourth temperature zone is 255°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the temperature of the seventh temperature zone is 260°C, and the temperature of the eighth temperature zone is 260°C. The temperature of the ninth temperature zone is 260℃, the temperature of the tenth temperature zone is 260℃, the temperature of the eleventh temperature zone is 255℃, the temperature of the twelfth temperature zone is 240℃, the screw speed of the twin-screw extruder is 400r / min, the extruder head temperature is 240℃, the melt pressure is 10MPa, the vacuum pressure is -0.05MPa, the main engine current is 200A, the torque is 15N·m, the aspect ratio is 60:1, the speed of the pelletizer is 3500r / min, and the length of the laser engraving masterbatch is 4mm.
[0058] Comparative Example 1 Preparation method of polyester substrate laser engraving masterbatch: Step 1: Weigh the following components: 85 parts by weight of polyester substrate, 10 parts by weight of laser engraving powder, 10 parts by weight of titanium dioxide, 3 parts by weight of pigment, 0.5 parts by weight of compound stabilizer, 3 parts by weight of dispersant, and 0.5 parts by weight of crosslinking agent. When the pressure of polyester substrate is 0.45 MPa, the heat deformation temperature is 68°C, the tensile strength is 25 MPa, the elongation at break is 112%, and the impact strength of cantilever beam notch is 7.1 KJ / M 2 The polyester substrate is PN300 produced by SK Company of South Korea. The polyester substrate is dried before preparing laser engraving masterbatch. The drying temperature is 65℃ and the drying time is 8 hours. The laser engraving powder is in powder form with a particle size of 7um and a specific gravity of 1.5g / cm 3 The heat-resistant temperature is 220℃. The laser engraving powder model is 8808 in the Iriotec series produced by Merck, USA. The surface of titanium dioxide is coated with zirconium aluminum. Titanium dioxide is a white powder with a titanium dioxide content of 95%. The specific gravity of titanium dioxide is 4.5g / cm 3The pigment is red and has a heat-resistant temperature of 300°C. The compound stabilizer is a mixture of a heat stabilizer and a light stabilizer, and the ratio of the heat stabilizer to the light stabilizer is 1:10. The heat stabilizer is a mixture of a metal soap stabilizer and an antioxidant, and the ratio of the metal soap stabilizer to the antioxidant is 1:10. The metal soap stabilizer is zinc stearate, and the zinc content in zinc stearate is 13%. The melting point of calcium stearate is 120°C. The antioxidant includes a primary antioxidant and an auxiliary antioxidant. The primary antioxidant is tris(2,4-di-tert-butylphenyl) phosphite, and the auxiliary antioxidant is dilauryl thiodipropionate. The light stabilizer is phenylbenzotriazole and diisopropyl ester. The invention discloses a mixture of 2,2,6,6-tetramethyl-4-piperidinyl sebacate, wherein the ratio of phenylbenzotriazole to bis-2,2,6,6-tetramethyl-4-piperidinyl sebacate is 1:10; the dispersant is a mixture of high molecular weight amino-modified silicone resin and high molecular weight hyperbranched polymer, wherein the ratio of high molecular weight amino-modified silicone resin to high molecular weight hyperbranched polymer is 1:2, the viscosity of the high molecular weight amino-modified silicone resin is 6500 mPa·s, the dynamic friction coefficient is 0.13, and the acid value of the high molecular weight hyperbranched polymer is 580 mgKOH / g; and the crosslinking agent is diphenylmethane diisocyanate.
[0059] Step 2: Mixing materials: Take the above-mentioned laser carving powder, titanium dioxide, pigment, compound stabilizer, dispersant, polyester substrate and cross-linking agent and stir and mix them in a high-stirring pot to obtain a mixed material, wherein the stirring temperature of the high-stirring pot is 55°C, the stirring speed is 150r / min, and the stirring time is 1min.
[0060] Step 3: Granulation: Take the mixed material and feed it through the main feeding port of the twin-screw extruder, then extrude it through the twin-screw extruder, cool it, and cut it into pellets to obtain the polyester base laser engraving masterbatch. The twin-screw extruder is divided into 12 temperature zones. The temperature of the first temperature zone is 230°C, the temperature of the second temperature zone is 235°C, the temperature of the third temperature zone is 235°C, the temperature of the fourth temperature zone is 235°C, the temperature of the fifth temperature zone is 235°C, the temperature of the sixth temperature zone is 235°C, the temperature of the seventh temperature zone is 240°C, and the temperature of the eighth temperature zone is The temperature of the ninth temperature zone is 250℃, the temperature of the tenth temperature zone is 255℃, the temperature of the eleventh temperature zone is 230℃, the temperature of the twelfth temperature zone is 230℃, the screw speed of the twin-screw extruder is 300r / min, the extruder head temperature is 230℃, the melt pressure is 8MPa, the vacuum pressure is -0.08MPa, the main engine current is 150A, the torque is 13N·m, the aspect ratio is 55:1, the speed of the pelletizer is 3000r / min, and the length of the laser engraving masterbatch is 3mm.
[0061] Comparative Example 2 Preparation method of polyester substrate laser engraving masterbatch: Step 1: Weigh the following components: 85 parts by weight of polyester substrate, 10 parts by weight of laser engraving powder, 10 parts by weight of titanium dioxide, 3 parts by weight of pigment, 0.5 parts by weight of stabilizer, 3 parts by weight of dispersant, and 0.5 parts by weight of crosslinking agent. When the pressure of the polyester substrate is 0.45 MPa, the heat deformation temperature is 68°C, the tensile strength is 25 MPa, the elongation at break is 112%, and the impact strength of the cantilever beam notch is 7.1 KJ / M 2 The polyester substrate is PN300 produced by SK Company of South Korea. The polyester substrate is dried before preparing laser engraving masterbatch. The drying temperature is 65℃ and the drying time is 8 hours. The laser engraving powder is in powder form with a particle size of 7um and a specific gravity of 1.5g / cm 3 The heat-resistant temperature is 220℃. The laser engraving powder model is 8808 in the Iriotec series produced by Merck, USA. The surface of titanium dioxide is coated with zirconium aluminum. Titanium dioxide is a white powder with a titanium dioxide content of 95%. The specific gravity of titanium dioxide is 4.5g / cm 3 The pigment is red and has a heat-resistant temperature of 300°C. The stabilizer is zinc stearate, the zinc content in zinc stearate is 13%, and the melting point of zinc stearate is 120°C. The dispersant is a mixture of a high molecular weight amino-modified silicone resin and a high molecular weight hyperbranched polymer, the ratio of the high molecular weight amino-modified silicone resin to the high molecular weight hyperbranched polymer is 1:2, the viscosity of the high molecular weight amino-modified silicone resin is 6500mPa·s, the dynamic friction coefficient is 0.13, and the acid value of the high molecular weight hyperbranched polymer is 580mgKOH / g. The cross-linking agent is diphenylmethane diisocyanate.
[0062] Step 2: Mixing materials: Take the above-mentioned laser carving powder, titanium dioxide, pigment, stabilizer and dispersant, stir and mix them in a high-stirring pot to obtain mixed material 1, wherein the stirring temperature of the high-stirring pot is 75°C, the stirring speed is 250r / min, and the stirring time is 2min.
[0063] Step 3: Mixing material: Take the above polyester substrate and cross-linking agent and stir and mix them in a high-stirring pot to obtain a mixed material 2, wherein the stirring temperature of the high-stirring pot is 55° C., the stirring speed is 150 r / min, and the stirring time is 1 min.
[0064] Step 4: Granulation: Take the mixed material 1 and the mixed material 2 and feed them simultaneously through the main feeding port of the twin-screw extruder, extrude them through the twin-screw extruder, cool them, and cut them into pellets to obtain the polyester base laser engraving masterbatch. The twin-screw extruder is divided into 12 temperature zones, the temperature of the first temperature zone is 230°C, the temperature of the second temperature zone is 235°C, the temperature of the third temperature zone is 235°C, the temperature of the fourth temperature zone is 235°C, the temperature of the fifth temperature zone is 235°C, the temperature of the sixth temperature zone is 235°C, the temperature of the seventh temperature zone is 240°C, and the temperature of the eighth temperature zone is 240°C. The temperature of the first temperature zone is 250℃, the temperature of the ninth temperature zone is 250℃, the temperature of the tenth temperature zone is 255℃, the temperature of the eleventh temperature zone is 230℃, and the temperature of the twelfth temperature zone is 230℃. The screw speed of the twin-screw extruder is 300r / min, the extruder head temperature is 230℃, the melt pressure is 8MPa, the vacuum pressure is -0.08MPa, the main engine current is 150A, the torque is 13N·m, the aspect ratio is 55:1, the speed of the pelletizer is 3000r / min, and the length of the laser engraving masterbatch is 3mm.
[0065] Comparative Example 3 Preparation method of polyester material: Step 1: Weigh 90 parts of polyester resin, 8 parts of flame retardant, 3 parts of nano-silica coated mica powder, 0.7 parts of black masterbatch, 1 part of antioxidant, and 1 part of lubricant, and mix them evenly in a blender; Step 2: Feed the raw materials from the main feeding port and melt extrude at 200-280°C. The extruder screw diameter is 42mm, the aspect ratio is 35, the screw extruder speed is 700rpm, and the pressure is 2MPa. After melt extrusion and granulation, the polyester material is obtained.
[0066] The clarity, uniformity and accuracy of laser engraving in Examples 1-3 and Comparative Examples 1-3 are shown in Table 1: Table 1 Comparison of laser engraving clarity, uniformity and accuracy in Examples 1-3 and Comparative Examples 1-3
[0067] Note: Comparison of laser engraving effects: High > Medium > General In summary, in the prior art (Comparative Examples 1-3), the overall effect of laser engraving is not good enough. Comparative Example 1 does not adopt a special order of adding materials, but only mixes all the materials at once, which results in average uniformity of laser engraving, and medium clarity and accuracy of laser engraving. Comparative Example 2 does not use a compound stabilizer, but only uses zinc stearate, a metal soap stabilizer, which results in average clarity and accuracy of laser engraving, and medium uniformity of laser engraving. Comparative Example 3 uses nano-silicon dioxide-coated mica powder to ensure high clarity of laser engraving, but low uniformity and accuracy of laser engraving. Therefore, Examples 1-3 of the present invention adopt a special order of adding materials and use a compound stabilizer to ensure that the clarity, uniformity and accuracy of laser engraving of polyester-based laser engraving masterbatch reach a high level, that is, the present invention produces unexpected technical effects.
[0068] The above description is only a preferred embodiment of the present invention and does not constitute any other form of limitation to the present invention. Any modification or equivalent change made based on the technical essence of the present invention still falls within the scope of protection required by the present invention.
Claims
1. A polyester-based laser engraving masterbatch, characterized in that: The laser engraving masterbatch comprises the following components: Polyester substrate: 70-100 parts by weight; Laser carving powder: 1-20 parts by weight; Titanium dioxide: 0-20 parts by weight; Pigment: 0-5 parts by weight; Compound stabilizer: 0.1-1 parts by weight; Dispersant: 0.5-5 parts by weight; Cross-linking agent: 0.1-1 parts by weight.
2. The laser engraving masterbatch according to claim 1, characterized in that: When the pressure of the polyester substrate is 0.45 MPa, the thermal deformation temperature is 65-75°C.
3. The laser engraving masterbatch according to claim 1, characterized in that: The laser engraving powder is in powder form, with a particle size of 5-10um and a specific gravity of 1.5-2g / cm 3 , heat-resistant temperature is 200-300℃.
4. The laser engraving masterbatch according to claim 1, characterized in that: The compound stabilizer is a mixture of a heat stabilizer and a light stabilizer, and the ratio of the heat stabilizer to the light stabilizer is (1-10): (1-10).
5. The laser engraving masterbatch according to claim 4, characterized in that: The heat stabilizer is a mixture of a metal soap stabilizer and an antioxidant, and the ratio of the metal soap stabilizer to the antioxidant is (1-10): (1-10).
6. The laser engraving masterbatch according to claim 5, characterized in that: The metal soap stabilizer is calcium stearate or zinc stearate.
7. The masterbatch according to claim 5, characterized in that The antioxidant comprises a primary antioxidant and a secondary antioxidant, wherein the primary antioxidant is one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol ester, tris(2,4-di-tert-butylphenyl)phosphite or bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite, and the secondary antioxidant is one of tris(2,4-di-tert-butylphenyl)phosphite, dilauryl thiodipropionate or bis(2,4-di-tert-butylphenol)sulfide, and the primary antioxidant and the secondary antioxidant are mixed in any proportion.
8. The laser engraving masterbatch according to claim 4, characterized in that: The light stabilizer is a mixture of phenylbenzotriazole and bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate, and the ratio of the phenylbenzotriazole to the bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate is (1-10):(1-10).
9. A method for preparing the laser engraving masterbatch according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: Step 1: Weigh each component; Step 2: Mixing materials: taking the laser carving powder, the titanium dioxide, the pigment, the compound stabilizer and the dispersant, stirring and mixing in a high-stirring pot to obtain a mixed material 1; Step 3: Mixing material: taking the polyester substrate and the cross-linking agent and stirring and mixing them in a high-stirring pot to obtain a mixed material 2; Step 4: Granulation: Take the mixed material 1 and the mixed material 2 and feed them simultaneously through the main feeding port of the twin-screw extruder, extrude them through the twin-screw extruder, cool them, and pelletize them to obtain the polyester-based laser engraving masterbatch.
10. The method according to claim 9, characterized in that In the step 4, the twin-screw extruder is divided into 12 temperature zones, the temperature of the first temperature zone is 220-245°C, the temperature of the second temperature zone is 225-250°C, the temperature of the third temperature zone is 225-250°C, the temperature of the fourth temperature zone is 225-255°C, the temperature of the fifth temperature zone is 225-260°C, the temperature of the sixth temperature zone is 225-260°C, the temperature of the seventh temperature zone is 230-260°C, the temperature of the eighth temperature zone is 240-260°C, the temperature of the ninth temperature zone is 240-260°C, the temperature of the tenth temperature zone is 245-260°C, the temperature of the eleventh temperature zone is 220-255°C, and the temperature of the twelfth temperature zone is 220-240°C.
Citation Information
Patent Citations
Polyester material suitable for laser graving and preparation method thereof
CN109370166A